Conflict the history of the Korean War, 1950-1953 - Leckie, Robert (Da Capo Press, 1996)
"In June 1950 Communist forces poured across the 38th Parallel (the arbitrary, militarily indefensible line of latitude separating the Communist North from the independent Republic of Korea) to unite t"